Evaluasi Tingkat Kapabilitas Keamanan Sistem Informasi Menggunakan Kerangka Kerja Cobit 2019 - Acihmah Sidauruk; Asro Nasiri (LPPM STMIK IKMI Cirebon, 2022)
Abstract- Organizational dependence on information technology support is getting bigger. An increase in information security must accompany the use of information technology. Information is currently a vital asset for the XYZ university; therefore, an evaluation of how well the controls and activities are in protecting information assets needs to manage at the XYZ university. The assessment uses the COBIT 2019 framework in the APO12, APO13, and DSS05 domains to identify XYZ university's capability in managing information security. The evaluation results show that information security management at XYZ University is still at capability level 2 for the APO12, APO13, and DSS05 domains. There are 17 recommendations for improving the implementation of information security.